Seis nuevas referencias de cianofíceas para la Península Ibérica. - Temes-casas, M.; Noguerol-seoane, Ángela (Botanica Complutensis, 2001)
TEMES-CASAS, M. & NOGUEROL-SEOANE, A. 2001. Six new records of cyanophytes for the Iberian Peninsula. Botanica Complutensis 25: 155-164. Six taxa of cyanoprokaryotes founded in the Lourido's river basin are reported in this paper: Chamaesiphon minutus (Rostafinski) Lemmermann, Cyanostylon sp., Arthrospira skujae (Schmidle) Magrin, Symploca laete-viridis Gomont, Rivularia hansgirgi Schmidle and Stigonema mirabile Beck v. Mannagetta. All of them are new records for the Iberian Peninsula. A detailed description and figures of each taxon are given.
Keywords: Cyanoprokaryota; Cyanophyceae; freshwater; Galicia; Spain